Diversity and Abundance of Dacinae Fruit Flies (Insecta: Diptera: Tephritidae) in Pantai Melawi and Selising, Kelantan, Peninsular Malaysia. - Yong, Hoi Sen; Hashim, Rosli; Azirun, Mohd Sofian; Mat Diah, Siti Zaleha (Malaysian Journal of Science, 2010)
The diversity and abundance of Dacinae fruit flies of the family Tephritidae were studied at Pantai Melawi (Bachok) and Selising (Pasir Puteh), Kelantan. Male fruit flies were collected in the morning by using the attractants methyl eugenol and cue-lure. Three species (Bactrocera carambolae, Bactrocera papayae and Bactrocera melastomatos) were present in both localities, with B. papayae and B. melastomatos being more abundant in Pantai Melawi and B. carambolae more abundant in Selising. Bactrocera caudata occurred only in Pantai Melawi while Bactrocera umbrosa only in Selising. The two localities supported different species of Dacinae fruit flies and different density of the common species